Re-engineering Business Processes in the New Normal - The Business and Economic Development Post COVID-19 and the Restructuring of the Global Economy: Proceedings of 8th International Conference on Business and Management Dynamics - Michael Twum-Darko (Re-engineering Business Processes in the New Normal - The Business and Economic Development Post COVID-19 and the Restructuring of the Global Economy: Proceedings of 8th International Conference on Business and Management Dynamics, 2023)
The investigated the effect of social capital on the performance of SMMEs. The book discussed the impact of existing government policy on entrepreneurial activities in a Province in South Africa. Also, the book reveals the perceptions and experiences of small and medium enterprise owners from the tourism sector towards the COVID-19 pandemic in South Africa. Furthermore, the book investigated how social listening tools, such as EARS, can contribute to global health during an infodemic using South Africa as the context of the study to discuss the EARS tool. The book also determined the student perceptions of having to adapt to online learning in the Department of Accounting at a traditional university. The contribution of this book extends to the examination of the negative effects of workplace bullying as a stressor on employees’psychological wellbeing and how the availability of social support can reduce the negative effects of bullying. It further explores how processes can be enhanced by making use of employee participation and employee involvement structures in organisations. Finally, the book explores perceptions of possible antecedents of effective corporate governance within Eastern Cape Public Entities of South Africa. Social sciences research methodology framework such as structured and sequential research process where each stage feeding into the other have provided an all-inclusive base for the entire social sciences research practice in this book. Some of the studies in this book also used quantitative research approach and descriptive research design in order to determine influences and practices associated with the phenomena being studies.